Effects of Major Spore-Specific DNA Binding Proteins on Bacillus subtilis Sporulation and Spore Properties - Setlow, Barbara (American Society for Microbiology, 2000)
Sporulation of a Bacillus subtilis strain (termed α(−) β(−)) lacking the majority of the α/β-type small, acid-soluble spore proteins (SASP) that are synthesized in the developing forespore and saturate spore DNA exhibited a number of differences from that of the wild-type strain, including delayed forespore accumulation of dipicolinic acid, overexpression of forespore-specific genes, and delayed expression of at least one mother cell-specific gene turned on late in sporulation, although genes turned on earlier in the mother cell were expressed normally in α(−) β(−) strains. The sporulation defects in α(−) β(−) strains were corrected by synthesis of chromosome-saturating levels of either of two wild-type, α/β-type SASP but not by a mutant SASP that binds DNA poorly. Spores from α(−) β(−) strains also exhibited less glutaraldehyde resistance and slower outgrowth than did wild-type spores, but at least some of these defects in α(−) β(−) spores were abolished by the synthesis of normal levels of α/β-type SASP. These results indicate that α/β-type SASP may well have global effects on gene expression during sporulation and spore outgrowth.